Celebrity worship and body image among young girls fans of K-pop girl groups - Kadek Ayu Anatasya Divina Tresna; Monique Elizabeth Sukamto; Marselius Sampe Tondok (HUMANITAS: Indonesian Psychological Journal, 2021)
Currently, K-pop girl groups are some of the favorite celebrities who often become the ideal standard for young girls. K-pop girl figures are often displayed with ideal body standards, such as having a slim body, white skin, thin face, and high nose, thus making fans adore and want to have a physical appearance like their idol. This study aimed to examine the relationship between celebrity worship and body image among female adolescents who idolized K-pop girl groups. A sample of 414 female adolescents aged 18-22 years participated online in the current study by filling in the Celebrity Attitude Scale (CAS) and the Multidimensional Body-Self Relation Questionnaire-Appearance Scale (MBSRQ-AS). Results showed that the entertainment-social aspect of celebrity worship proved a significant positive correlation with the appearance orientation dimension of body image. In contrast, the borderline-pathological aspect had a significant negative correlation with the body areas satisfaction dimension. Nonetheless, the intense personal aspect of celebrity worship did not correlate significantly with all dimensions of body image among young girls fans of K-pop girl groups. Thus, each level of celebrity worship correlates differently with each dimension of body image. Entertainment-social is the most common celebrity worship among adolescent girls fans of K-pop girl groups and affects young girls' body image by increasing their attention to appearance.